Molecular data reveal hidden diversity of the genus Clinostomum (Digenea, Clinostomidae) in Argentina, with the description of a new species from Ardea cocoi (Ardeidae) - Montes, Martín Miguel (2021)
The genus Clinostomum has been recently a subject of a large number of molecular phylogenetic studies that have uncovered a larger species diversity than we thought. In Argentina, only two nominal species have been reported, namely C. detruncatum and C. marginatum. Three putative species represented by metacercariae were recently molecularly diagnosed, and there are at least two additional metacercarial morphotypes diagnosed on morphological grounds. Here, we molecularly characterized specimens of Clinostomum sampled from freshwater fishes and fish-eating birds from Argentina through mtDNA cytochrome c oxidase subunit I (COI). Unexpectedly, the phylogenetic analysis uncovered three new additional genetic lineages, two of them corresponding to metacercarial stages and another matching COI sequences of C. heluans Braun, 1899, being considered conspecific, whereas the others still require formal description. Additionally, we add a new host species for a lineage molecularly diagnosed in a previous study. The adult specimens recovered from A. cocoi in Buenos Aires Province represented a new species clearly distinguished from the two species previously reported in Argentina. Clinostomum detruncatum is distinguished from the new species by possessing a characteristic tenoidean uterus, and testes located more posteriorly. Clinostomum marginatum is morphologically similar but differs from the new species in having rounded ovary, posterior testis lobated, and lateral cirrus-sac and displacing the anterior testis, and vitelline follicles not extending beyond the caeca end. Our study raises the number of Clinostomum species in Argentina up to 10. We describe the new species herein.